2001
DOI: 10.1542/peds.108.6.e111
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Pediatric After-Hours Care by Call Centers: A Multicenter Study of Parental Perceptions and Compliance

Abstract: ABSTRACT. Background. Despite the rapid growth of centralized call centers to provide after-hours triage to patients of multiple providers, little is known about the perceptions of parents regarding this type of care and their compliance with triage disposition recommendations.Design/Methods. From August through September 1999, randomized samples of after-hours calls were selected each day from computerized records at 4 pediatric call centers at 1) Children's Hospital, Denver, Colorado; 2) Children's Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 11 publications
2
38
0
3
Order By: Relevance
“…We do know that callers often do not follow the advice given by telephone triage. 15 However, regardless of what the individual caller did, our ability to track appointments showed that the overall appointment fill rates changed much less than expected for the call volumes. We were also unable to do a more robust time series analysis of the data.…”
Section: Discussionmentioning
confidence: 79%
“…We do know that callers often do not follow the advice given by telephone triage. 15 However, regardless of what the individual caller did, our ability to track appointments showed that the overall appointment fill rates changed much less than expected for the call volumes. We were also unable to do a more robust time series analysis of the data.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, parents have reported both high [12,13] and low [14] satisfaction with the telephone service. Examples of dissatisfaction include parents who felt they were not treated with respect [15] , and fathers who rated service quality lower than mothers [16] .…”
mentioning
confidence: 99%
“…This is richly illustrated in experience with the ''mother of all'' connected health services, telephone management, a service presently with well-established effectiveness and efficiency. [33][34][35][36][37][38][39][40][41][42][43] Phone management guidelines addressing illness manifestations of children and adults lead to specific recommendations for home management or inperson visits. If the latter, the time frame is also specified (e.g., see in office within 72 h, go to emergency department now, call 911).…”
Section: Discussionmentioning
confidence: 99%